History of the Christian church ; v.3 - Sheldon, Henry C. (Peabody, MA Hendrickson, 1988)
Contents : v.3 : The modern church ; pt 1 : 1517-1720. Includes bibliographical references and indexes.
Reprinted from the original edition, published 1895, Thomas Y. Crowell and Co., New York.
Keywords: Church history -- modern period -- 1500-.; Reformation